Twenty-Year Trends in Antimicrobial Susceptibilities Among Staphylococcus aureus From the SENTRY Antimicrobial Surveillance Program - Diekema, Daniel J; Pfaller, Michael A; Shortridge, Dee; Zervos, Marcos; Jones, Ronald N (Open forum infectious diseases, 2019)
Abstract Background Staphylococcus aureus is among the most common human pathogens, with therapy complicated by the epidemic spread of methicillin-resistant Staphylococcus aureus (MRSA). Methods The SENTRY Antimicrobial Surveillance Program evaluated the in vitro activity of >20 antimicrobials against 191 460 clinical S. aureus isolates collected from 427 centers in 45 countries from 1997 to 2016. Each center contributed isolates and clinical data for consecutive episodes of bacteremia, pneumonia in hospitalized patients, urinary tract infection, and skin and skin structure infection. Results Overall, 191 460 S. aureus isolates were collected, of which 77 146 (40.3%) were MRSA, varying geographically from 26.8% MRSA in Europe to 47.0% in North America. The highest percentage of MRSA was in nosocomial isolates from patients aged >80 years. Overall, MRSA occurrences increased from 33.1% in 1997–2000 to a high of 44.2% in 2005–2008, then declined to 42.3% and 39.0% in 2009–2012 and 2013–2016, respectively. S. aureus bacteremia had a similar trend, with nosocomial and community-onset MRSA rates peaking in 2005–2008 and then declining. Vancomycin activity against S. aureus remained stable (minimum inhibitory concentration [MIC]90 of 1 mg/L and 100% susceptibility in 2016; no increase over time in isolates with a vancomycin MIC >1 mg/L). Several agents introduced during the surveillance period exhibited in vitro potency against MRSA. Conclusions In a large global surveillance program, the rise of MRSA as a proportion of all S. aureus peaked a decade ago and has declined since, consistent with some regional surveillance program reports. Vancomycin maintained high activity against S. aureus, and several newer agents exhibited excellent in vitro potencies.